Phenolic Contents and Antioxidant Activities of Various Infused Tea Liquids Made from Leaves of Green Tea (Camellia sinensis), Banaba (Lagestroemia speciosa) and Moringa (Moringa oleifera L.) - Rufnia Ayu Afifah; Chutamat Niwat (Universitas Teuku Umar, 2020)
Plants, such as as green tea (Camellia sinensis), banaba (Lagestroemia speciosa) and moringa (Moringa oleifera L.), have been known as the basis of traditional medicine that have been existed for thousands years due to their bioactive compounds. This research aimed to investigate total phenolic content and antioxidant properties of various tea infusion made from green tea, moringa and banaba leaves. Dried green tea, dried banaba leaves, and fresh moringa leaves were used in this study. Fresh moringa leaves then was dried at two different temperatures (50 and 60 ºC). The results showed that the total phenolic content of tea infusions were ranged from 11–20 mg GAE/g, while the DPPH scavenging activity and FRAP activity ranged from 6–12 µmol TE/g, 0.2–0.65 mmol FeSO4/g, respectively. Banaba tea had the highest total phenolic content (20.54±0.31 mg GAE/g), DPPH (11.19±0.12 µmol TE/g), and FRAP activity (0.66±0.02 mmol FeSO4/g) compared to another infused tea (P<0.05). Higher drying temperature (60 ºC) of moringa leaves reduced the total phenolic content in the moringa tea. However, it had no effect to the DPPH scavenging activity and FRAP activity (P<0.05). In conclusion, the total phenolic content and antioxidant activities were varied by tea leaf variations and drying condition.